2021
DOI: 10.25034/ijcua.2021.v5n1-3
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization, Housing Quality and Health: Towards a Redirection for Housing Provision in Nigeria

Abstract: Nigeria’s housing provision is perceived in terms of quantity with less attention to its quality and impact on people’s health. The quality of indoor air in housing and its associated risks to human health was assessed in this paper to improve housing provision in Nigeria. Quantitative data collected from Bauchi, Nigeria includes household surveys, housing characteristics, indoor carbon dioxide (CO2), and particulate matter (PM2.5 and PM10). PM2.5 and PM10 recorded in the building were (63 μm/m3) and (228 μm/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Proactive spatial interventions of environmental factors in residential areas can improve residents' health. [54][55][56][57][58][59][60][61][62][63][64] However, research on the impact of built environment quality elements on the subjective well-being of older people after the quality of the neighborhood environment in settlements has been improved is lacking. The study examines the current practice of multi-quality renewal in existing Dalian neighborhoods, examining the differences in the impact of multi-quality elements on the subjective well-being of the older adults in different neighborhood environment types, and observing the degree of change in the subjective well-being of the older adults from the standpoint of psychological resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proactive spatial interventions of environmental factors in residential areas can improve residents' health. [54][55][56][57][58][59][60][61][62][63][64] However, research on the impact of built environment quality elements on the subjective well-being of older people after the quality of the neighborhood environment in settlements has been improved is lacking. The study examines the current practice of multi-quality renewal in existing Dalian neighborhoods, examining the differences in the impact of multi-quality elements on the subjective well-being of the older adults in different neighborhood environment types, and observing the degree of change in the subjective well-being of the older adults from the standpoint of psychological resilience.…”
Section: Discussionmentioning
confidence: 99%
“…31 As a result, mental activity and emotional affect are often used as a manifestation or moderator of well-being, as well as ways to express well-being. 53 Some studies have also found a strong link between the residential environment, housing, and health, [54][55][56][57][58][59][60][61][62][63][64] and Li Shuran and Chen Changhui argue that paying attention to the special needs of the older adults for their living environment is beneficial to their physical and mental health; 54 Zhang and Lin et al proactive spatial interventions in residential environmental factors can have a positive impact on residents' health and promote China's health. 55 Currently, there has been little research on the impact of built environment quality elements on the subjective wellbeing of older people following environmental quality improvements (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…This testifies to the fact that the rest of the cities of Ukraine are significantly behind the modern world indicators and trends in the maintenance, development and increase of urban space greening. This negative result, must be taken into account when developing master plans for cities [14,15].…”
Section: Ukraine's Place In the Ranking Of The Greenest Cities In The...mentioning
confidence: 99%
“…These have evolved into the perfect breeding grounds for new illnesses like the worldwide coronavirus pandemic and the Ebola epidemics in Africa. Urbanization and other significant urban development trends must be managed immediately to safeguard and advance health (Akande, 2021). To accomplish this and address the problems caused by urbanisation, particularly in the Global South, urban housing has emerged as one of the important players.…”
Section: Introductionmentioning
confidence: 99%